Interaction flow modeling language model-driven ui engineering of web and mobile apps with ifml - Brambilla, Marco; Fraternali, Piero (Elsevier, 2015)
Interaction Flow Modeling Language describes how to apply model-driven techniques to the problem of designing the front end of software applications, i.e., the user interaction. The book introduces the reader to the novel OMG standard Interaction Flow Modeling Language (IFML). Authors Marco Brambilla and Piero Fraternali are authors of the IFML standard and wrote this book to explain the main concepts of the language. They effectively illustrate how IFML can be applied in practice to the specification and implementation of complex web and mobile applications, featuring rich interactive interf.
Includes bibliographical references and index. - Print version record
Keywords: User interfaces (Computer systems); Programming languages (Electronic computers); User-Computer Interface; Interfaces utilisateurs (Informatique)